2006
DOI: 10.1002/ajmg.a.31127
|View full text |Cite
|
Sign up to set email alerts
|

Primary palmar hyperhidrosis locus maps to 14q11.2‐q13

Abstract: Primary palmar hyperhidrosis (PPH) is a unique disorder of unknown cause. It is characterized by excessive perspiration of the eccrine sweat gland in the palm, sole, and the axilla. It is presumed that PPH results from overactivation of the cholinergic sympathetic nerve or dysfunction of the autonomic nervous system. There have been no genetic studies on the disease. We performed a linkage analysis of 11 families including 42 affected and 40 unaffected members using genome-wide DNA polymorphic markers to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 21 publications
(23 reference statements)
3
29
1
2
Order By: Relevance
“…The condition affects both males and females, principally individuals of Japanese descent. [1][2][3] There are idiopathic primary forms and those that occur secondary to hyperthyroidism, menopause, obesity, panic syndrome, alcoholism, neoplastic conditions or medication. The condition may affect the skin of the entire body or be limited to the palmoplantar region, axillae, inframammary, inguinal, intergluteal or craniofacial regions.…”
Section: Comunicationmentioning
confidence: 99%
“…The condition affects both males and females, principally individuals of Japanese descent. [1][2][3] There are idiopathic primary forms and those that occur secondary to hyperthyroidism, menopause, obesity, panic syndrome, alcoholism, neoplastic conditions or medication. The condition may affect the skin of the entire body or be limited to the palmoplantar region, axillae, inframammary, inguinal, intergluteal or craniofacial regions.…”
Section: Comunicationmentioning
confidence: 99%
“…Man vermutet ein autosomal-dominantes Vererbungsmuster mit Lokalisation des verantwortlichen Gens auf Chromosom 14. Aufgrund nur unvollständiger Penetranz kommt es nicht in allen Fällen zur Manifestation [12,21]. Die primäre Hyperhidrose tritt am häufigsten in umschriebenen Körperarealen auf, v. a. im Bereich der Axillen, aber auch an Händen, Füßen, im Gesicht und Nacken, seltener sind mehrere Areale oder der gesamte Körper betroffen [25,31].…”
Section: Klassifikationunclassified
“…In 57% of cases, there is a positive family history [3]. Some articles have reported that PH is an autosomal dominant disorder with variable penetration in chromosomes 5 or 14 or both; in some cases congenital factors are involved [4,5].…”
Section: Introductionmentioning
confidence: 99%